Preparation and Application of ZnFe2O4/α-Al2O3 for Photocatalytic Degradation of Methylene Blue Dye and Real Textile Effluent - Abdulhamid Hamza; Alhaji Saleh Zanna Umara; Diya'uddeen Basheer Hasan (Aceh International Journal of Science and Technology, 2019)
Present work was aimed at the development of α-Al2O3 supported ZnFe2O4 visible-light responsive photocatalysts. ZnFe2O4 and α-Al2O3 supported ZnFe2O4 were synthesized using co-precipitation method followed by calcination at 500 °C. The synthesized photocatalysts were characterized using x-ray diffraction (XRD) and scanning electron microscopy (SEM). The synthesized ZnFe2O4 has low crystallinity.  The particle size of ZnFe2O4 is much smaller than that of the α-Al2O3 support, and ZnFe2O4 particles are dispersed on the surface of the crystalline α-Al2O3 support. 30 wt % ZnFe2O4/α-Al2O3 exhibited the highest photocatalytic activity for degradation of methylene blue dye than ZnFe2O4 and other α-Al2O3 supported photocatalysts containing 10 wt%, 20 wt% and 40 wt% ZnFe2O4. Kinetics of photocatalytic degradation of methylene blue dye using 30 wt% ZnFe2O4/Al2O3 obeys Langmuir–Hinshelwood kinetic model. Photocatalytic treatment of real textile wastewater resulted in more effective (when compared to photolytic treatment) in the reduction of wastewater’s chemical oxygen demand (COD), pH, conductivity and total dissolved solids (TDS). 30 wt% ZnFe2O4/Al2O3 was found to be more effective than unsupported ZnFe2O4 for the reduction of wastewater’s COD, pH, conductivity and TDS.